Differences in hemoglobin levels in anemic pregnant women before and after administration of iron supplement tablets and dragon fruit - Wulandari, Fitra; Santy, Eka; Yulianti, Emy (Borneo Scientific Publishing, 2024)
Pregnancy is a much-anticipated period for every married couple. The health of the mother during pregnancy is very important because there is a fetus that is growing and developing, and it is hoped that the baby will be born healthy and become a quality future generation. Based on the 2018 Basic Health Research (Riskesdas), the prevalence of anemia in pregnant women in Indonesia in 2018 increased by 48.9% from 37.1% in 2013. Iron supplementation (TTD) was provided to 73.2% of pregnant women, with 24% receiving 90 tablets or more and 76% receiving less than 90 tablets. The government has implemented an IFT program, but the prevalence of anemia remains high. The purpose of this study was to determine the difference in hemoglobin (Hb) levels in pregnant women with anemia before and after receiving iron tablets and dragon fruit in the working area of the Wajok Hulu Community Health Center. This study used a quasi-experimental research design with a non-equivalent control group or non-randomized control group pretest-posttest design. The study population consisted of pregnant women with anemia who were registered in the Wajok Hulu Community Health Center area from January to May 2019. The sampling technique used total sampling, with a sample size of 16 people. The statistical test used was the paired t-test, and the normality test used was the Shapiro-Wilk test. The results of the study showed that there was no difference in the effect of administering iron tablets and dragon fruit, and only iron tablets based on changes in hemoglobin levels in pregnant women in the working area of the Wajok Hulu Community Health Center in 2019 with a p-value of 0.766 and a difference value of 0.09.